Flagging greens: hydrobiid snails as substrata for the development of green algal mats (Enteromorpha spp.) on tidal flats of North Atlantic coasts - Schories, D. (2000)
During the past 3 decades, dense mats of green algae (especially Enteromorpha spp.) have been recorded regularly from tidal flats worldwide. The development of green algal mats on tidal flats may be initiated by overwintering and regrowth of adult plants or by the formation and release of small propagules, i.e. vegetative fragments, zoospores and zygotes. On soft sediments, macroinvertebrates may constitute prime substrata for germination of algal spores. Hydrobud (mud-) snails are widespread along North Atlantic soft sediment shores and were identified previously as important substrata for Enteromorpha spp. germlings in 1 of our study areas. To test the generality of this phenomenon, we investigated the presence of Enteromorpha spp. gerrnlings attached to hydrobud snails from November 1995 to December 1996 on 6 tidal flats of North Atlantic coasts (Tralebergslule, Sweden; Konigshafen Bay, Germany; Mondego Estuary, Portugal; Ria Formosa, Portugal; Cole Harbour, Nova Scotia, Canada; Lowes Cove, Maine, USA). With 1 exception, hydrobiid snails were present in all areas studied, and intensive growth of Enteromorpha spp. occurred during summer. Throughout winter 1995/96, hardly any Enteromorpha spp. gerrnlings were found on snail shells, but over the following months germlings developed on up to 60% of the hydrobiid snails present. In 2 areas (Konigshafen, Germany; Lowes Cove, USA), germhng abundance on hydrobuds began to rise before the peak of green algal mat development. In Tralebergskile, Sweden, high mat abundance occurred simultaneous to and after increased germling abundance on Hydrobia ulvae. Densities of snails were very low, however, and hydrobuds appeared to be unimportant as substratum. No clear temporal pattern between high germling abundance on snails followed by mat development was found in the other 3 study areas (Ria Formosa, Portugal; Mondego Estuary, Portugal; Cole Harbour, Canada). In Lowes Cove, USA, gerrnlings and juveniles of Enteromorpha spp. first grew at the site with high Hydrobia abundance and were subsequently drifted to another site where they developed into full mats. We conclude that initiation of green algal mats by germination on Hydrobia spp. may be a general phenomenon, but that other modes of development also occur frequently. Pelagic dnft of overwintering thalli to new sites, followed by prolific growth, might be of similar or greater importance.